Modulation of dendritic AMPA receptor mRNA trafficking by RNA splicing and editing - La Via, Luca; Bonini, Daniela; Russo, Isabella; Orlandi, Cesare; Barlati, Sergio; Barbon, Alessandro (Nucleic acids research, 2013)
RNA trafficking to dendrites and local translation are crucial processes for superior neuronal functions. To date, several α-amino-3-hydroxy-5-methyl-4-isoxazolepropionate receptor (AMPAR) mRNAs have been detected in dendrites and are subject to local protein synthesis. Here, we report the presence of all AMPAR GluA1-4 mRNAs in hippocampal and cortical rat synaptic spines by synaptoneurosomes analysis. In particular, we showed that dendritic AMPAR mRNAs are present in the Flip versions in the cortex and hippocampus. To further confirm these data, we demonstrate, using in situ hybridization, the dendritic localization of the GluA2 Flip isoform in vitro and in vivo, whereas the Flop variant is restricted mainly to the soma. In addition, we report that dendritic AMPA mRNAs are edited at low levels at their R/G sites; this result was also supported with transfection experiments using chimeric GluA2 DNA vectors, showing that transcripts carrying an unedited nucleotide at the R/G site, in combination with the Flip exon, are more efficiently targeted to dendrites when compared with the edited-Flip versions. Our data show that post-transcriptional regulations such as RNA splicing, editing and trafficking might be mutually coordinated and that the localization of different AMPAR isoforms in dendrites might play a functional role in the regulation of neuronal transmission.